PENGARUH GOOD CORPORATE GOVERNANCE TERHADAP NILAI PERUSAHAAN MELALUI CORPORATE SOCIAL RESPONSIBILITY - Bambang Soedaryono; Deri Riduifana (Media Riset Akuntansi, Auditing & Informasi, 2013)
This research aims to obtain empirical evidence about the direct effect of GoodCorporate Governance (GCG) on firm value and the indirect effect of GCG on firm value through Corporate Social Responsibility (CSR). Good Corporate Governance elements which were used in this research, board of director size, number of board of director meetings, number of board independent commissioner, number of audit committee meetings, nomination and remuneration committee. This research also used firm’s size, firm’s age and type of industry as control variable. The population of this research was all companies that listed in Indonesian Stock Exchange (IDX) in 2010. Total sample in this research are 215 firms that selected with purposive sampling. Structural Equation Modeling (SEM) was used to analyze the direct and indirect effect of GCG on firm value through CSR. The result of this research indicates that the GCG which shown as number of board of director have significant direct effect influence on firm value, meanwhile for the indirect effect number of audit committee meetings has significant influence on firm value through CSR. The firm’s size and type of industry as variable control also have a significant influence on CSR, meanwhile firm’s age have no significant influence on CSR.